Science Education for Students with Special Needs in Indonesia: From Definition, Systematic Review, Education System, to Curriculum - Rina Maryanti; Asep Bayu Dani Nandiyanto; Achmad Hufad; S. Sunardi (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to determine the teaching, curriculum, and methods used by teachers in the science learning process for students with special needs in Indonesia. We use qualitative research methods. The subjects in this study are students with special needs (children with visual impairments, children with hearing impairments, children with intellectual disabilities, and children with physical impairments) at one of the special schools (SLB) in Kuningan, Indonesia. The results show that most of the teachers use the curriculum from teacher books provided by the government. In addition, some teachers used the lecture and question and answer method in the science learning process. The results in low student achievement because students with special needs need concrete media and methods that accommodate student needs.